Keeping up the balance: role of HDACs in cardiac proteostasis and therapeutic implications for atrial fibrillation. (8th December 2015) - Zhang, Deli; Hu, Xu; Henning, Robert H.; Brundel, Bianca J.J.M.
Abstract: Cardiomyocytes are long-lived post-mitotic cells with limited regenerative capacity. Proper cardiomyocyte function depends critically on the maintenance of a healthy homeostasis of protein expression, folding, assembly, trafficking, function, and degradation, together commonly referred to as proteostasis. Impairment of proteostasis has a prominent role in the pathophysiology of ageing-related neurodegenerative diseases including Huntington's, Parkinson's, and Alzheimer's disease. Emerging evidence reveals also a role for impaired proteostasis in the pathophysiology of common human cardiac diseases such as cardiac hypertrophy, dilated and ischaemic cardiomyopathies, and atrial fibrillation (AF). Histone deacetylases (HDACs) have recently been recognized as key modulators which control cardiac proteostasis by deacetylating various proteins. By deacetylating chromatin proteins, including histones, HDACs modulate epigenetic regulation of pathological gene expression. Also, HDACs exert a broad range of functions outside the nucleus by deacetylating structural and contractile proteins. The cytosolic actions of HDACs result in changed protein function through post-translational modifications and/or modulation of their degradation. This review describes the mechanisms underlying the derailment of proteostasis in AF and subsequently focuses on the role of HDACs herein. In addition, the therapeutic potential of HDAC inhibition to maintain a healthy proteostasis resulting in a delay in AF onset and progression is discussed.